Systematic analysis of splicing defects in selected primary immunodeficiencies-related genes - Grodecká, Lucie; Hujová, Pavla; Kramárek, Michal; Kršjaková, Tereza; Kováčová, Tatiana; Vondrášková, Katarína; Ravčuková, Barbora; Hrnčířová, Kristýna; Souček, Přemysl; Freiberger, Tomáš (Clinical immunology (Orlando, Fla.), 2017)
Both variants affecting splice sites and those in splicing regulatory elements (SREs) can impair pre-mRNA splicing, eventually leading to severe diseases. Despite the availability of many prediction tools, prognosis of splicing affection is not trivial, especially when SREs are involved. Here, we present data on 92 in silico-/55 minigene-analysed variants detected in genes responsible for the primary immunodeficiencies development (namely BTK, CD40LG, IL2RG, SERPING1, STAT3, and WAS). Of 20 splicing-affecting variants, 16 affected splice site while 4 disrupted potential SRE. The presence or absence of splicing defects was confirmed in 30 of 32 blood-derived patients' RNAs. Testing prediction tools performance, splice site disruptions and creations were reliably predicted in contrast to SRE-affecting variants for which just ESRseq, ΔHZEI-scores and EX-SKIP predictions showed promising results. Next, we found an interesting pattern in cryptic splice site predictions. These results might help PID-diagnosticians and geneticists cope with potential splicing-affecting variants.
Keywords: messenger RNA; buňky Hep G2; kojenec; komplement C1 - inaktivátory; U937 Cells; transkripční faktor STAT3; Protein-Tyrosine Kinases; HeLa Cells; sestřih RNA; Exons; mutace; Splicing prediction; Infant; Hep G2 Cells; Immunologic Deficiency Syndromes; syndromy imunologické nedostatečnosti; dítě; Child; Interleukin Receptor Common gamma Subunit; Complement C1 Inactivator Proteins; Splicing-affecting variants; Child, Preschool; inhibiční protein komplementu C1; Mutation; RNA, Messenger; Humans; předškolní dítě; Cryptic splice sites; Recombinant Fusion Proteins; protein Wiskottova-Aldrichova syndromu; receptory interleukinů - společná gama-podjednotka; rekombinantní fúzní proteiny; Complement C1 Inhibitor Protein; U937 buňky; STAT3 Transcription Factor; tyrosinkinasy; Wiskott-Aldrich Syndrome Protein; Agammaglobulinaemia Tyrosine Kinase; Primary immunodeficiencies; RNA Splicing; exony; proteinkinasa BTK; HeLa buňky; lidé